Design of the RINSE trial: The rapid infusion of cold normal saline by paramedics during CPR - Deasy, C.; Bernard, S.; Cameron, P.; Jacobs, Ian; Smith, K.; Hein, C.; Grantham, H.; Finn, Judith (BioMed Central Ltd., 2011)
Background: The International Liaison Committee on Resuscitation (ILCOR) now recommends therapeutic hypothermia (TH) (33°C for 12-24 hours) as soon as possible for patients who remain comatose after resuscitation from shockable rhythm in out-of-hospital cardiac arrest and that it be considered for non shockable rhythms. The optimal timing of TH is still uncertain. Laboratory data have suggested that there is significantly decreased neurological injury if cooling is initiated during CPR. In addition, peri-arrest cooling may increase the rate of successful defibrillation. This study aims to determine whether paramedic cooling during CPR improves outcome compared standard treatment in patients who are being resuscitated from out-of-hospital cardiac arrest. Methods/Design:This paper describes the methodology for a definitive multi-centre, randomised, controlled trial of paramedic cooling during CPR compared with standard treatment. Paramedic cooling during CPR will be achieved using a rapid infusion of large volume (20-40 mL/kg to a maximum of 2 litres) ice-cold (4°C) normal saline. The primary outcome measure is survival at hospital discharge. Secondary outcome measures are rates of return of spontaneous circulation, rate of survival to hospital admission, temperature on arrival at hospital, and 12 month quality of life of survivors. Discussion: This trial will test the effect of the administration of ice cold saline during CPR on survival outcomes. If this simple treatment is found to improve outcomes, it will have generalisability to prehospital services globally.